PEMBERDAYAAN GURU DAN SISWA MELALUI LITERASI DIGITAL BERBASIS QR CODE DI ERA PERKEMBANGAN TEKNOLOGI - Mohammad Syaiful Pradana; Nisaul Barokati Selirowangi; Aslichatul Jannah; Ahmad Haris; Samsul Huda (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2023)
Today's digital developments provide easy access for everyone to obtain knowledge and information. But in fact, not all of them are able to adapt quickly to digital developments. One of them is in terms of digital literacy that has penetrated the world of education. In community service this aims to empower teachers and students of SDN Munungrejo-Ngimbang Lamongan through digital literacy based on the Quick Response Code (QR Code). The method of implementing community service goes through several stages, namely (1) socialization of digital literacy, (2) production of digital literacy, (3) printing of digital literacy, (4) delivery of digital literacy, (5) utilization of digital literacy for training, (6) sharing digital literacy, (7 ) Practice digital literacy. The results of this QR code-based digital literacy community service activity received a positive response at the Munungrejo Elementary School, they believed that the activities carried out were very useful as a medium for gaining knowledge for both students and teachers. The Quick Response Code on digital literacy also has an impact on growing interest in reading among students at SDN Munungrejo-Ngimbang Lamongan.